Cold dwell behaviour of Ti6Al alloy: Understanding load shedding using digital image correlation and dislocation based crystal plasticity simulations. (20th November 2022) - Xiong, Yi; Grilli, Nicolò; Karamched, Phani S.; Li, Bo-Shiuan; Tarleton, Edmund; Wilkinson, Angus J.
Highlights: The cold dwell behaviour of Ti6Al is analysed by a combination of digital image correlation, electron backscatter diffraction and dislocation based crystal plasticity simulations Experiments and simulations are carried out between room temperature and 230°C to understand the worst case scenario for cold dwell and understand its physical origin A data set of pairs of grains is analysed: some pairs of grains show the "rogue" and "non-rogue" behaviour respectively, while a novel behaviour called "non-typical rogue" is observed, in which a moderate load shedding takes place during cold dwell The correlation between stress discontinuity at the grain boundary in "rogue" grain pairs and the distribution of geometrically necessary dislocations is analysed The worst case scenario at 120°C is explained by the temperature dependence of the strain rate sensitivity of basal and prismatic slip systems, and the temperature dependence of the spread of geometrically necessary dislocations around the grain boundary Abstract: Digital image correlation (DIC) and dislocation based crystal plasticity simulation were utilised to study cold dwell behaviour in a coarse grain Ti-6Al alloy at 3 different temperatures up to 230 °C. Strains extracted from large volume grains were measured during creep by DIC and were used to calibrate the crystal plasticity model. The values of critical resolved shear stresses (CRSS) of the two main slip systems (basal and prismatic) were determined as a function of temperature. Stress along paths across the boundaries of four grain pairs, three "rogue" grain pairs and one "non-rogue" grain pair, were determined at different temperatures. Large load shedding was observed in one of the "rogue" grain pairs, where a stress increment during the creep period was found in the "hard" grain. A minor load shedding mechanism was observed in two non-typical "rogue" grain pairs, in which the plastic deformation is nonuniform inside the grains and geometrically necessary dislocations accumulate in the centre of the grains. At elevated temperatures, 120 °C was found to be the worst case scenario as the stress difference at the grain boundaries of these four grain pairs was found to be the largest among the three temperatures analysed. The origin of this critical temperature is debated in the literature and it is investigated for the first time in the present work by analysing the simultaneous effects of the geometrically necessary dislocations (GND) and the strain rate sensitivity (SRS) of the slip systems. The analysis shows that the combined effects of the peak SRS of both prismatic and basal slip systems at 80 °C and of the increase of the spread of the GND distribution around the grain boundary at higher temperatures are the origin of the observed worst case scenario. Graphical abstract: Image, graphical abstract